Author Correction: Complete elimination of information leakage in continuous-variable quantum communication channels. (December 2018) - Jacobsen, Christian; Madsen, Lars; Usenko, Vladyslav; Filip, Radim; Andersen, Ulrik
In the original published version of the Article, the inline equation for the conditional covariance matrixγ A |B was listed asγ A |B =γ A −γ B, 11 −1 C ΠC . This equation should be γA |B = γA − γB, 11 −1 σAB Π σAB . This has now been corrected in the PDF and HTML versions of the Article.